Thermal decomposition behavior of water hyacinth (eichhornia crassipes) under an inert atmosphere - Sukarni Sukarni (MATEC Web of Conferences, 2018)
Thermogravimetric analysis experiment to understand thermal decomposition behavior of water hyacinth during the pyrolysis has been performed. Water hyacinth was taken randomly from 2 places, i.e., Selorejo and Sengguruh Dam, district of Malang, Indonesia. Those raw materials were thoroughly cleaned by using the water, then cut and dried in an oven with a temperature range of 80-90 °C for 6 hours. Subsequently, the dried samples were crushed and then filtered to a mesh size of 60. Thermal behavior of the sample was observed through the instrumentality of thermal analyzer at a constant heating rate of 10 °C/min with a nitrogen flow rate of 100 ml/min and a temperature range of 25-1000 °C. The kinetics of active pyrolysis zone were evaluated by Coats-Redfern integral method. The thermogravimetric test results show that the water hyacinth biomass decomposed into four stages during the pyrolysis process. The kinetic parameters in term of activation energy (E), logarithmic frequency factor (log A) and reaction order (n) were 60.74 kJ/mol, 4.77/min and 1.9, respectively.